[A06] Sex Specific Differences in Pre-operative Standard of Care for Infrarenal AAA Repair and Association with Peri-operative Major Adverse Cardiovascular Events and Death. (November 2022) - Pouncey, Anna Louise; Martin, Guy; Bicknell, Colin; Sweeting, Michael; Powell, Janet
Abstract : Objective: Following elective infrarenal abdominal aortic aneurysm (IRAAA) repair, women have a higher rate of major adverse cardiovascular events and death (MACED). Disparity in pre-operative standard of care (SOC) may contribute. Methods: Elective IRAAA repair data from the National Vascular Registry, 2013 – 2020 were analysed. SOC was defined for pre-operative assessment (multidisciplinary/anaesthetic review), waiting times, and cardiovascular risk prevention. Analyses and multivariable logistic regression were conducted according to a pre-specified plan. Results: There were 21 810 patients (2 380 women; 19 430 men). Women were less often repaired within SOC waiting times (51.5% vs . 59.6%, p < .01), but received similar SOC pre-operative assessment (72.1% vs . 72.5%, p not significant). Women had ischaemic heart disease less often (29.0% vs . 37.7%, p < .01), but those with known cardiovascular co-morbidity received SOC risk prevention more often (52.1% vs. 47.3%, p < .01). Overall, women were less likely to receive antiplatelets (72.2% vs . 75.2%, p < .01) or statins (77.1% vs . 80.6%, p < .01). Women were at greater risk of MACED following open (12% vs . 8.9%, p < 0.01) and endovascular (4.9 % vs. 2.9%, p < .01) repair: overall odds ratio (OR) 1.51, adjusted for age and repair type; OR 1.28 following adjustment for demographics, co-morbidities and SOC. SOC waiting time was associated with a reduction in risk (OR 0.79) for both sexes. SOC pre-operative assessment reduced MACED risk for women (OR 0.80), but not men (OR 1.09). SOC cardiovascular risk prevention did not significantly influence MACED risk. Conclusion: Treatment within SOC waiting time is independently associated with a reduction in MACED risk for both sexes, SOC pre-operative assessment is associated with risk reduction for women only.